Assessing the process for induction of labour: effect on service rationalisation. (16th November 2010) - Higgins, L; Mahoney, C; Baker, A; Gillham, J; Tower, C
Abstract : Background: One in five pregnant women in the United Kingdom undergo induction of labour (IOL), occupying a significant number of maternity beds. Concerns over delays in IOL processes prompted evaluation and modification of this service in our unit. Our objective was to reduce admission to delivery times (ADT), increase vaginal delivery rates and assess secondary outcomes including postpartum haemorrhage (PPH) rates following IOL. Methods: 262 admissions for IOL were reviewed in three cycles over 15 months. Following cycle 1, midwives were trained to conduct IOL and an IOL proforma introduced. After cycle 2, a dedicated four-bed IOL bay was introduced. IOL was conducted with prostaglandin gel, followed by artificial rupture of membranes and oxytocin. Statistical significance was tested using one-way analysis of variance (Kruskal–Wallis) for ADT and χ 2 test for vaginal delivery and PPH rates. Results: See table. Abstract PL.02 Cycle 1 2 3 p Value Number of patients 100 80 82 ADT (Hours) (Median, IQR) 37.72 (27.73–59.91) 29.79 (14.42–48.74) 28.07 (17.70–45.16) 0.004 Vaginal delivery (%) 67.68 77.50 74.39 0.32 PPH (%) 37.11 35.44 32.10 0.7 Conclusion: The training of midwives to conduct IOL and provision of a dedicated IOL bay have resulted in a significant fall in median ADT from 37.72 to 28.07 h, but no significant change in vaginal delivery or PPH rates. These changes may result in improved efficiencies to the NHS but further work is required to investigate patient satisfaction and to reduce residual delays in the IOL process at our unit.